Foreign commerce during the 19th century in Tradiciones peruanas - Huamán Pinedo, Viviana (2021)
This article will deal with the result of the research of «Origen de una industria» and «Garantido, todo lino», texts that are part of the Tradiciones peruanas of the great «Bibliotecario Mendigo» don Ricardo Palma. We are interested in emphasising the importance of foreign commerce during the Republican era, as well as the impact and changes that it had on the Peruvian people.